2005
DOI: 10.1079/pgr200594
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic erosion of traditional vegetables in Tanzania from the farmer's point of view

Abstract: Traditional vegetables in Tanzania have been underutilized by farmers and neglected by research and development programmes. In the framework of the project 'Promotion of Neglected Indigenous Vegetable Crops for Nutritional Health in Eastern and Southern Africa' led by the World Vegetable Center (AVRDC) and partners, focus group meetings were conducted in 10-12 villages in each of four districts of north-east Tanzania, which differed in ethnicity as well as in altitude, climate and soil conditions. Farmers name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 11 publications
1
118
3
1
Order By: Relevance
“…WEPs can contribute to food security in several ways. Harvesting and trading WEPs can result in rural employment and income generation (Shackleton and Shackleton 2004;Akinnifesi et al 2005; Keller et al 2006;Agea et al 2007;Barucha and Pretty 2010;Legwaila et al 2011). In other studies, the incorporation of WEPs in cropping systems has increased agro-biodiversity, enhanced production and mitigated the effects of environmental shocks, pests and diseases (Moore and Raymond 2006;Tilman et al 2006;Venter et al 2007;Frison et al 2011;Mahapatra and Panda 2012;Asif and Kamran 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WEPs can contribute to food security in several ways. Harvesting and trading WEPs can result in rural employment and income generation (Shackleton and Shackleton 2004;Akinnifesi et al 2005; Keller et al 2006;Agea et al 2007;Barucha and Pretty 2010;Legwaila et al 2011). In other studies, the incorporation of WEPs in cropping systems has increased agro-biodiversity, enhanced production and mitigated the effects of environmental shocks, pests and diseases (Moore and Raymond 2006;Tilman et al 2006;Venter et al 2007;Frison et al 2011;Mahapatra and Panda 2012;Asif and Kamran 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, WEPs are adapted to the local and sometimes harsh environmental conditions where other cultivated species would fail (Bradford 2010;Flyman and Afolayan 2006). Because of their resilience, WEPs can act as safety nets in times of food shortage and famine (Guinand and Dechassa 2000;Shackleton and Shackleton 2004;Kebu and Fassil 2006;Keller et al 2006). They may also contribute to greater dietary diversity and be essential components of an otherwise monotonous and nutritionally poor diet (Grivetti and Ogle 2000;FAO 2005;Fentahun and Hager 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Higher on-farm agro-biodiversity in traditionally managed as compared to intensified agricultural production systems was also found in Ghana (Awanyo 2007), Nigeria (Netting and Stone 1996), Tanzania (Keller et al 2006) and Peru (Pinedo-Vasquez et al 2002). The last authors showed that traditional smallholder farming systems can manage agricultural activities while conserving agro-biodiversity.…”
Section: Agro-biodiversity and Soil Degradation Changes (2000-2005)mentioning
confidence: 86%
“…The last authors showed that traditional smallholder farming systems can manage agricultural activities while conserving agro-biodiversity. Netting and Stone (1996) and Keller et al (2006) attributed the loss of agro-biodiversity to changes in land use resulting from socio-cultural and economic changes, such as expansion of urban areas and use of modern crop varieties. Agrobiodiversity decline on agricultural lands was also reported from the central Himalaya in India mainly because of changes in agricultural land use (Maikhuri et al 2001), rapid socio-economic changes (replacement of mixed crops with uniform cash crops, changes in food habits, changes in social integration) and cultural changes (changes in traditional wisdom, faith and beliefs) (Nautiyal et al 2008).…”
Section: Agro-biodiversity and Soil Degradation Changes (2000-2005)mentioning
confidence: 99%
“…A shift to simplified and monotonous diets, from the diversified traditional diets has resulted in increased consumption of staple foods, and a decrease in the consumption of traditional foods including forest foods that are abundantly and locally available within the region (Keller et al, 2006;Frison et al, 2006;Pingali, 2007;Penafiel et al, 2011). Negative perceptions towards forest foods have been documented among rural communities in South Africa (Dweba and Mearns, 2011) and in Togo (Akpavi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%